2019
DOI: 10.17323/jle.2019.8822
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vocabulary Knowledge on the Reading Comprehension of Saudi EFL Learners

Abstract: Vocabulary knowledge is the building block of learning a second language and the degree of success for learning any language depends on the amount of vocabulary a learner possesses. Vocabulary knowledge contributes to mastering language skills (reading, listening, writing, and speaking). Therefore, the present study aims at determining the role of vocabulary size in reading comprehension among Saudi EFL learners. The participants of this study included 64 male students who studied at the first level in the aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The findings revealed that there were significant differences between the experimental and control groups' mean learner autonomy scores and learners showed positive views towards MALL and technology-based language learning (Behforouz & Frumuselu, 2020). Considering the unavoidable relationship between lexical knowledge and reading comprehension discussed in many studies (Al-Khasawneh, 2019;Jamalipour &Farahani, 2015;Kamal, 2019;Karakoç & Köse, 2017;Rydland, et al, 2012;Zhang & Annual, 2008), this study aims to analyze the effect of text messaging on EFL learners' vocabulary depth and breadth. Few studies could be found in the literature that applied SMS text messaging to pre-teaching vocabulary to EFL learners in Iran.…”
Section: Texting In Educationmentioning
confidence: 97%
“…The findings revealed that there were significant differences between the experimental and control groups' mean learner autonomy scores and learners showed positive views towards MALL and technology-based language learning (Behforouz & Frumuselu, 2020). Considering the unavoidable relationship between lexical knowledge and reading comprehension discussed in many studies (Al-Khasawneh, 2019;Jamalipour &Farahani, 2015;Kamal, 2019;Karakoç & Köse, 2017;Rydland, et al, 2012;Zhang & Annual, 2008), this study aims to analyze the effect of text messaging on EFL learners' vocabulary depth and breadth. Few studies could be found in the literature that applied SMS text messaging to pre-teaching vocabulary to EFL learners in Iran.…”
Section: Texting In Educationmentioning
confidence: 97%
“…Grabe and Stroller (2001) emphasize the role of large vocabulary knowledge in reading comprehension. Similarly, Al-Khasawneh (2019) says that the relationship between vocabulary and reading comprehension is a "robust" one and that vocabulary knowledge has consistently been the "foremost predictor of a text's difficulty" (p.241). Furthermore, vocabulary knowledge is a major prerequisite and causal factor in reading comprehension because the reader has to know the actual words in the text to be able to comprehend it (Tavanpour and Biria, 2017).…”
Section: Alls 12(2):59-69mentioning
confidence: 99%
“…In the same vein, Abedi (2017) found that lack of familiarity with vocabulary knowledge in test passages was an important element affecting EFL learners on a reading comprehension test. Al-Khasawneh (2019) and Altalhab (2019) found that the strength of the relationship between word knowledge and reading ability of EFL students increased as their grade level progressed.…”
Section: Alls 12(2):59-69mentioning
confidence: 99%
See 1 more Smart Citation
“…Vocabulary knowledge plays an essential role in literacy development and academic success. It supports the mastering of reading, speaking, listening, and writing skills (Al-Khasawneh, 2019;Silsüpür, 2017). Scholars have acknowledged the importance of vocabulary in second language (L2) learning and language use.…”
Section: Introductionmentioning
confidence: 95%